Marketing and promotion of regional trade inforamtion services - McBean, Vince (CEDP St. MichaelBD, 1992)
Confirms that there is a substantial demand for trade information both within the region and beyond and acknowledges that this market demand is constantly changing and new priorities are continually emerging. Consequently the participation by other information suppliers and quick responses are important. Both private and public sector channels must therefore play a role in the marketing of information to users, as no single marketing channel can reach the entire spectrum of user groups. Posits that networks work best.